A germline mutation in the BRCA13’UTR predicts stage IV breast cancer - Dorairaj, Jemima J.; Salzman, David W.; Wall, Deirdre; Rounds, Tiffany; Preskill, Carina; Sullivan, Catherine AW; Lindner, Robert; Curran, Catherine; Lezon-Geyda, Kim; McVeigh, Terri; Harris, Lyndsay; Newell, John; et al. (BMC cancer, 2014)
A germline, variant in the BRCA1 3’UTR (rs8176318) was previously shown to predict breast and ovarian cancer risk in women from high-risk families, as well as increased risk of triple negative breast cancer. Here, we tested the hypothesis that this variant predicts tumor biology, like other 3’UTR mutations in cancer.